Redox regulation of memory formation by Rrp1 in Drosophila. - Hsu, C.T.; Chen, C.C.; Hung, Y.L.; Yang, Y.T.; Chiu, Y.H.; Fong, S.S.; Yang, J.H.; Wu, Z.W.; Liou, J.W.; Lin, H.W.; Feng, K.L.; Yang, J.L.; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2025)
Long-term memory (LTM) formation requires precise gene regulation, yet the role of redox activity in this process remains poorly understood. Here, we identify Drosophila recombination repair protein 1 (Rrp1), a homolog of human apurinic/apyrimidinic endonuclease 1 (APE1), as a key redox regulator of LTM. In paired dorsal-anterior-lateral neurons-critical for aversive olfactory memory-Rrp1 knockdown impairs memory formation, whereas its overexpression enhances retention. Pharmacological inhibition of Rrp1 redox activity with E3330 suppresses Period and CaMKII expression, disrupting LTM formation. Notably, human APE1 redox activity rescues memory deficits in Rrp1-deficient flies, promotes de novo Period synthesis, and facilitates LTM formation. Moreover, Rrp1 is required for CREBA-mediated LTM acceleration, revealing a redox-dependent link between transcriptional regulation and memory persistence. These findings establish Rrp1 as a critical modulator of LTM in Drosophila and highlight redox regulation as a conserved mechanism underlying memory formation.